PEMIKIRAN TEOLOGI FAZLUR RAHMAN - Ramadhan, Muhammad (TEOLOGIA, 2014)
Abstract: The development of Islamic modern theology becomes moral obligation for us which live as the biggest Moslem in the world. Fazlur Rahman laid stress on his discussion on the problem of God as the funnctional existence, the Quran as moral source and value, and the prophecy as concrete evidence of Allahâs affection, and the human as the creature to be responsibility for.Â  Similarly he discussed on the universe to be processed, satan as as test for mankind, and the hereafter life as the place for mankind liability. All themes were discussed in a discourse which for specific boundaries show the dynamic. Acccording to Rahman there are some problems of theology if they related to ethic in the Quran.It is not perfect discussion that can be carried out except if we willing to end with disclosure of all the contents of Quran. Having relation to this issue, he offered to read the Quran with the Quran itself. Abstrak: Pengembangan pemikiran teologi modern Islam semakin terasa menjadi kewajiban moral kita yang hidup sebagai bangsa muslim terbesar di muka bumi ini. Fazlur Rahman menitik beratkan bahasannya sekitar persoalan tuhan sebagai eksistensi yang fungsional, al-Quransebagai sumber dan nilai moral, dan kenabian sebagai bukti kongkrit kepengasihan Allah, sertaÂ  manusia sebagai mahluk yang berÂtanggung jawab. Demikian pula ia mengangkat bahasan alam semesta untuk diolah, setan sebagai ujian bagi manusia, serta kehidupan akhirat sebagai tempat pertanggung jawaban manusia. Semua tema tersebut dibahas dalam satu wacana yang sampai batas-batas tertentu benar-benar menunjukkan dinamika. Begitu banyak menurut Rahman yang bisa kita bicarakan mengenai teologi jika dikaitkan dengan etika dalam al-Qurâan. Suatu pembicaraan yang sempurna tidak akan dapat dilakukan, kecuali kalau kita bersedia berakhir dengan pengungkapan seluruh isi kitab itu sendiri. Berkenaan dengan ini, Dan itupun tidak juga mungkin kecuali dalam bentuk membaca al-Quranitu sendiri, dan membiarkan kitab suci itu bicara sendiri. Fazlur Rahman pun gemar membuat pernyataan semacam itu. Keywords: teologi modern, nilai moral, Tuhan, al-Quran, setan, akhirat.